Quality assessment of Portuguese monofloral honeys. Physicochemical parameters as tools in botanical source differentiation - Machado, Alexandra M. (2022)
The quality evaluation and physicochemical parameters assessment of Portuguese monofloral honeys were performed. Fifty-one monofloral honeys were collected from several regions from mainland Portugal, and from the Azores islands, producer labelled as carob tree (n = 5), chestnut (n = 2), eucalyptus (n = 5), bell heather (n = 6), incense (n = 4), lavender (n = 8), orange (n = 9), rape (n = 2), raspberry (n = 2), rosemary (n = 1), sunflower (n = 3), and strawberry tree (n = 4). Pollen analysis and microbiological safety were evaluated, and the parameters such as colour index, moisture content, electrical conductivity, hydroxymethylfurfural, pH, free and total acidity, diastase activity, proline, and sugar profile were assessed for physicochemical characterization, in all 51 monofloral honeys. After melissopalynological examination, the honeys were either confirmed as monofloral, or classified as multifloral with predominance of a specific pollen type or multifloral. Microbiological analysis showed that honeys were safe for human consumption. Pairwise comparisons of physicochemical parameters, using only honey types with n >= 3, revealed significant differences between honey types. Despite some homogeneity in sugar profile among honeys, eucalyptus honey was significantly different in glucose, maltose and maltulose content compared to incense, orange and sunflower honeys, and also exhibited a higher isomaltose amount compared to all analyzed honeys. Electrical conductivity, colour index, free and total acidity, and diastase activity showed significant differences between the analyzed honeys, indicating that these parameters may provide an additional tool in monofloral honey identification.